The Mediation of Motivation on the Effects of Flexible Work Arrangements and Servant Leadership on Employee Performance during Covid-19 Pandemic - Puspita Arum Pamungkas; Siswoyo Haryono; Meika Kurnia Puji Rahayu D.A (Budapest International Research and Critics University, 2022)
The purpose of this study was to identify the mediation of motivation on the effect of flexible work arrangements and servant leadership on employee performance during the Covid-19 pandemic. This research data was obtained by distributing questionnaires to employees who work from home during the pandemic. The sampling technique used was purposive and convenience sampling. The data applied the SEM-PLS to analyze the proposed relationship model. The result of this study was (1) Flexible Work Arrangement affects motivation (2) Servant leadership affects motivation (3) Flexible work arrangements affects employee performance (4) Servant leadership affects employee performance (5) Motivation affects employee performance (6) Flexible work arrangement affects employee performance significantly through motivation (7) Servant leadership affects employee performance significantly through motivation. According to the research result, employee performance can be increased by motivation, flexible work arrangements, and servant leadership. Motivation as the mediating variable can be applied for flexible work arrangements and servant leadership to increase employee performance.